Mucinous Adenocarcinoma of the Rectum: A Whole Genome Sequencing Study - Reynolds, Ian S.; Thomas, Valentina; O’Connell, Emer; Fichtner, Michael; McNamara, Deborah A.; Kay, Elaine W.; Prehn, Jochen H. M.; Burke, John P.; Furney, Simon J. (Frontiers in Oncology, 2020)
Introduction: Mucinous adenocarcinoma of the rectum is an infrequently encountered histological subtype that is associated with an impaired response to chemoradiotherapy and a worse overall prognosis. A genomic profile analysis of mucinous rectal tumours has not yet been performed. The aim of this study was to comprehensively describe the burden of somatic mutations and copy number variation as well as perform mutational signature and microbial analysis of an in-house collected cohort of mucinous adenocarcinoma of the rectum. Methods: Genomic DNA was extracted from 10 cases of mucinous rectal cancer and matched normal tissue. Whole genome sequencing (WGS) was carried out on these 10 cases and a comprehensive bioinformatic analysis was undertaken. Results: The average number of SNVs, InDels and SVs in the cohort was 16,600, 1,855 and 120 respectively. A single case was MSI-H. KRAS mutations were found in 70% of cases while TP53 was mutated in only 40% of cases. CNA gain was identified on chromosomes 7, 8, 12, 13 and 20 while CNA loss was found on chromosomes 4, 8, 17 and 18 corresponding to oncogenes and tumour suppressor genes respectively. Overall mucinous rectal cancers are more likely to be MSI-H and to have KRAS, BRAF and PIK3CA mutations when compared to rectal adenocarcinoma NOS. Microbial analysis demonstrated an abundance of F. nucleatum in tumour samples compared to normal tissue. Conclusion: This study provides a detailed WGS analysis of 10 cases of mucinous rectal cancer. It demonstrates an important lesson in tumour biology in that histologically similar tumours can have extensive differences at the genomic level. This study is relevant as it raises important questions about the relationship between bacteria and malignancy.